Implementation of Random Shuffle Algorithm In "Hangbit" Education Games - Amelia Yusnita; Pajar Pahruddin; Theana Dwi Aprillita (TEPIAN, 2021)
Learning Media for Carnivorous Animals, Herbivorous Animals, Omnivorous Animals with PC-based Problem Randomization, an application designed to help students understand the introduction of carnivorous, herbivorous and omnivorous animals. The purpose of this study was to assist teachers in teaching lessons on introduction to carnivores, herbivores and omnivores, which consisted of animation, sound and text. This application was built using SwishMax4 and with the Shuffle Random Algorithm on learning questions so that it does not become a monotonous and predictable game. This study produces a multimedia application for learning advice on the introduction of carnivorous, herbivorous and omnivorous animals, so this learning medium is for children aged 7-10 years. The results of the study were tested on students of SD Negeri 010 Samarinda City by demonstrating the program and trying its application. The results of the making of this learning media are .Swf.